Novel Synthesis of Phytosterol Ester from Soybean Sterol and Acetic Anhydride. Issue 7 (30th May 2016) - Yang, Fuming; Oyeyinka, Samson A.; Ma, Ying
Abstract: Phytosterols are important bioactive compounds which have several health benefits including reduction of serum cholesterol and preventing cardiovascular diseases. The most widely used method in the synthesis of its ester analogous form is the use of catalysts and solvents. These methods have been found to present some safety and health concern. In this paper, an alternative method of synthesizing phytosterol ester from soybean sterol and acetic anhydride was investigated. Process parameters such as mole ratio, temperature and time were optimized. The structure and physicochemical properties of phytosterol acetic ester were analyzed. By the use of gas chromatography, the mole ratio of soybean sterol and acetic anhydride needed for optimum esterification rate of 99.4% was 1:1 at 135 °C for 1.5 h. FTIR spectra confirmed the formation of phytosterol ester with strong absorption peaks at 1732 and 1250 cm –1, which corresponds to the stretching vibration of C=O and C—O—C, respectively. These peaks could be attributed to the formation of ester links which resulted from the reaction between the hydroxyl group of soybean sterol and the carbonyl group of acetic anhydride. This paper provides a better alternative to the synthesis of phytosterol ester without catalyst and solvent residues, which may have potential application in the food, health‐care food, and pharmaceutical industries.